2015
DOI: 10.1097/inf.0000000000000559
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the 13-valent Pneumococcal Conjugate Vaccine on Nasopharyngeal Carriage of Streptococcus pneumoniae Among Children Attending Group Daycare in Southeastern France

Abstract: Regular surveys of pneumococcal nasopharyngeal carriage have been conducted among children attending daycare centers in Southeastern France from 1999 to 2012. We compared carriage rate, susceptibility patterns and serotype distribution in 2012, following implementation of the 13-valent pneumococcal conjugate vaccine, with findings from 5 previous surveys. Carriage rate was stable, antibiotic susceptibility improved and only serotype 19A persisted among vaccine-types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 9 publications
(4 reference statements)
4
15
3
2
Order By: Relevance
“…In reference to serotypes identified, a high proportion (76.8%) of NVT was found among carriers as previously reported [ 17 , 18 , 30 , 32 ]. Almost 50% of NP carriage was due to five serotypes, namely 23A/B, 6C and 15A/B ( Fig 1 ) as described by others [ 17 , 31 ]. Conversely to the above studies, serotypes 35B/F were less prevalent while we had no NP carriage by 11A.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In reference to serotypes identified, a high proportion (76.8%) of NVT was found among carriers as previously reported [ 17 , 18 , 30 , 32 ]. Almost 50% of NP carriage was due to five serotypes, namely 23A/B, 6C and 15A/B ( Fig 1 ) as described by others [ 17 , 31 ]. Conversely to the above studies, serotypes 35B/F were less prevalent while we had no NP carriage by 11A.…”
Section: Discussionsupporting
confidence: 81%
“…Fifteen children carried serotype 19A, two of which were fully vaccinated with PCV13. A recent study, evaluating the impact of PCV13 on NP carriage revealed that serotype 19A was the only persistent VT in the study population [ 17 ]. Lee et al found that the implementation of PCV13 in children 6–23 months of age in Massachusetts between 2007 and 2011 resulted in increased colonization with non-PCV13 serotypes.…”
Section: Discussionmentioning
confidence: 99%
“…13 However, while vaccine-type carriage has declined, VT pneumococci continue to be identified in 6% of children <5 years and 8% of infants in Kilifi, compared to <1-2% in other countries that use PCVs. [31][32][33][34][35] This may reflect a higher force of infection in Kilifi and it indicates continued risk for VT-IPD in unvaccinated or undervaccinated children, and adults. 36 An alternative explanation for the persistence of VT carriage in Kilifi is that, unlike most middle-income and high-income countries, Kenya introduced PCV10 without a booster dose in the second year of life.…”
Section: Discussionmentioning
confidence: 99%
“…31 Similarly, 3 years following the introduction of PCV13, Dunais showed that non-PCV13 strains accounted for 94% of nasopharyngeal carriage among healthy French children, with 15B/C and 35B among the most commonly identified types. 23 A recent US study showed 15% and 14% of pneumococcal isolates from the nasopharynx of 656 children in Atlanta were 35B and 15B/C, respectively. 35 Serotypes 35B and 15B/C have also been identified as increasing causes of IPD.…”
Section: Discussionmentioning
confidence: 99%
“…22 Similarly, carriage in French children decreased from 54% to 46% in a 3 year span. 23 In this work, we characterized pneumococcal nasopharyngeal carriage rates in HIV-infected adults following the introduction of PCV13 to the universal pediatric immunization schedule. In addition, we describe the serotype distribution and antibiotic susceptibility pattern for each of the isolates.…”
Section: Introductionmentioning
confidence: 99%